Safeguards against corruption in Roads Sector Procurement of works in Ghana - Bukari, Emmanuel Norgah (2014)
A thesis submitted to the Department of Building Technology, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of Master of Science (MSc) in Procurement Management